The Relationship between Smoking and The Incidence of Stroke at Haji Adam Malik General Hospital in 2018 - Tazzya Shailla Elfazi; Cut Aria Arina (Talenta Publisher, 2021)
Abstract. Stroke is a clinical sign that develops rapidly due to a disturbance of Focal (or global) brain function, with symptoms lasting for 24 hours or more, can lead to death, without any other cause than vascular. In Indonesia it is estimated that every year there are 500,000 inhabitants affected by stroke. One of the risk factors of stroke is the unhealthy lifestyle, such as smoking. The harmful content contained in cigarettes can become oxidizing substances in the blood so that there is damage to the artery walls and will be the location of fat-saving, platelet cells, cholesterol, and the thickening of the smooth muscle layers of the artery walls resulting in an aterotrombotic. This is what can cause a stroke. Goal. To know the relationship between smoking and the incidence of stroke in RSUP Haji Adam Malik Medan in 2018. Method. This type of research is analytic research with cross-sectional design. The data used in this research is secondary data that is data of the medical record of ischemic stroke patients and hemorrhagic stroke patients years 2018 obtained from RSUP Haji Adam Malik Medan medical record installation. The research method used is non-randomized consecutive sampling, with a side-total technique. The Data obtained is subsequently processed by computerization. Results. The hypothesis testing was conducted using a Chi-square test at a signification level of p < 0.05 and obtained a P value of 0.000 and also prevelence ratio > 1 with a value of 1.7418. Conclusion. There is a significant relationship between smoking and the incidence of stroke, especially in the event of ischemic stroke in RSUP Haji Adam Malik Medan in 2018.